RHYME TIME WITH PARROTS! - Edwards, Jonas (New York : Gareth Stevens Publishing, 2021)
"Parrots are known for their ability to repeat things that people say, but there's much more to know about these beautiful birds. With the help of this compelling volume, readers learn many amazing details about parrots-from where they live to what they eat-all with the help of rhymes. Engaging text is paired with colorful images, supporting readers of many ages and levels. Fun poems help impart key facts about these amazing animals in a way that will make readers want to keep turning the page!"
Let's see a parrot.
leveled reader science.
Includes index.
Keywords: Parrots -- Juvenile literature; Rhyme -- Juvenile literature